De capela filial a matriz paroquial : irmandades, jesuítas e territórios na Igreja do Rosário em Cuiabá-MT - Mendes, Marcos Amaral (2014)
ABSTRACT: Study of analytical-descriptive nature, “Nossa Senhora do Rosário” Church and “São Benedito” Chapel in Cuiabá are the themes of this work. From the perspective of a cultural reading in history, and in the treatment of long-term, it examines the experiences and experiments with the sacred and their territorial jurisdictions, trying to identify marks and relevant traits that shaped and directed the human actions and postures. The central assumption is that in different periods, historical contexts and spatiotemporal scales the temple met conditions to promote, structure and protect the existence of territories, expressed in everyday relationships, identity and perception recognition. This work adopts a qualitative and interpretive approach related to the problematized documentation from the present, in order to understand the diversity and uniqueness of practices, religious beliefs and behavior, as well as sociability and the bonds emerged in the spatial substrates. This study employs concepts and theories borrowed from other humanities areas and social sciences to enable the composition of a more complete picture of this reality. It aims to provide a contribution to the socioreligious culture lived in Cuiabá, result of many small pieces of time for its centurieslong history rescued by the researcher from a number of numbness files, now serving the community. The results indicate that the plurality of evocative signs and values related to the importance of this building, for city dwellers, extrapolates its architectural and artistic aspects, it is a practical and symbolic code that dialectically means and it’s meant, in which individuals and groups sought, generated and found their ways for their existence, one of the most significant references in the historicity of the capital of the state of Mato Grosso.